Faunos en los trópicos: modernismo y virilidad - Hernández Rodríguez, Rafael (Ecos y resplandores helenos en la literatura hispana: siglos XVI-XXI, 2018, ISBN 978-84-697-9697-9, págs. 113-130, 2018)
Modernism represents an artistic movement that mirrors the changing society of the late 19th century. This changing society produced the first cultural and artistic movement in Spanish America that asked what was this region's place in the Western World as well as what the poet's new function was. Among other issues that revea) the modernity of the movement, such as urbanization, industrialization, or the role of women, there is one of capital importance: the view of masculinity. This essay focuses on three texts that review the image of masculinity and art thought the figure of the faun. El modernismo representa un movimiento artístico que refleja la sociedad cambiante de finales del siglo XIX. Esta sociedad cambiante genera el primer movimiento cultural y artístico continental de importancia que intenta responder a la pregunta ¿cuál es el lugar de Hispanoamérica en el mundo occidental y cuál es la nueva función del poeta? Entre otros aspectos que señalan la modernidad del movimiento (como el urbanismo, la industrialización, el papel de la mujer), hay uno de particular importancia: la revisión de la masculinidad. Este ensayo se centra en tres textos que revisan la visión de la masculinidad y el arte a través de la imagen del fauno.
Section: Ecos y resplandores helenos en la literatura hispana: siglos XVI-XXI
Keywords: dept.wll

El silencio abyecto en la plaza del diamante - Weng, Miaowei (Boletín Redipe, 2018)
The article examines the gender roles imposed on women in Spain under the Franco regime. It revisits Mercè Rodoreda’s 1962 novel The Time of the Doves and deciphers the female protagonist’s silence in the context of the post-Civil War period. Drawing on Julia Kristeva’s conception of the abject, it explores how silence becomes informative of the protagonist’s mental resistance to the patriarchal imposition, the helplessness and powerlessness a common woman feels under the Franco regime, and the gradual growth of female subjectivity.
Citation Key Alias: lens.org/044-785-931-144-539, pop00351
Keywords: dept.wll; peer-reviewed; ⛔ No DOI found